Parametric studies of direct methanol fuel cell under different modes of operation - Farah Atiqah Abdullah,; Siti Kartom Kamarudin,; Azran Mohd Zainoodin,; Mohd Shahbudin Masdar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Direct methanol fuel cell (DMFC) performance tests were carried out in different modes of operation, namely, passive, active (air as oxidant) and active (oxygen as oxidant). Few parameters including methanol concentration (2 M, 4 M, 6 M, and 8 M) and methanol flow rate (1-4 mL min-1) were considered to investigate their effects on the DMFC performance. Fuel consumption was indicated by refractive index tests. Results showed that the performance of DMFC increased with the increase of methanol concentration and flow rate, until they reach certain values, i.e., 4-6 M and 2 mL min-1. Furthermore, for all parameters, the active mode with oxygen yielded the highest power density, followed by the active mode with air and passive DMFC system. The active mode with oxygen yielded the power density which peaks at 10.41 mW cm-2 during 6 M of methanol concentration and 2 mL min-1 rate of flowing methanol, followed by active mode with air at the cathode with 8.39 mW cm-2 and passive mode with 5.39 mW cm-2 respectively. It also records a better fuel consumption efficiency among all modes. These results indicate that investigating the level of fuel concentration and flow rate can lead to enhancement of mass transport and diffusion thus generating better performance of DMFC system.